The Historiography of Madrasah Education and Social Dynamics in Minangkabau - Yanti, Herina; Iswantir, Iswantir (The Future of Education Journal, 2025)
This article examines the historiography of madrasah education and the social dynamics of the Minangkabau community in West Sumatra, Indonesia. Using a qualitative-historical approach, this study analyzes how madrasah, as a traditional Islamic educational institution, has undergone transformation in line with social, cultural, and epistemological changes. The findings show that the historiography of madrasah in Minangkabau represents a dialectical relationship between religious orthodoxy and the currents of modernization. The historical narratives that have developed both in traditional surau chronicles and writings of reformers such as Mahmud Yunus and HAMKA reveal a paradigm shift from theocentric education to a rational and integrative model of Islamic education. Sociologically, madrasah plays a significant role in supporting the social structure of Minangkabau, which is based on the principle of "adat basandi syarak, syarak basandi Kitabullah" (custom based on sharia, sharia based on the Qur'an). Madrasah serves as a cultural and moral agent, bridging the values of tradition and religion, while also shaping collective identity and ethical consciousness in society. The transformation of the madrasah curriculum also shows an epistemological syncretism between Islamic studies and general knowledge, reflecting adaptation to modern educational paradigms. In facing the challenges of globalization and digital transformation, madrasah in Minangkabau is required to innovate pedagogically without losing its spiritual and cultural authenticity. This research offers a conceptual model of the Humanist-Integrative Madrasah, emphasizing the integration of Islamic values, local wisdom, and global competence. Thus, the historiography of madrasah in Minangkabau not only demonstrates the continuity of Islamic educational traditions but also its role as an agent of social transformation in the modern era.